Occupational Musculoskeletal Health Risks among Physical Therapists in Sindh: A Cross-Sectional Study - Wagan, Peraha; Faisal, Sidra; Pasham, Mukhry; Meraj, Munazzah; Mahrukh; Ahmed, Arsalan (Indus Journal of Bioscience Research, 2025)
Background: Musculoskeletal disorders (MSDs) are common occupational hazards among physical therapists, affecting their health and work performance. This study aimed to assess the prevalence and characteristics of low back, neck, and shoulder pain among physical therapists. Methods: A cross-sectional survey was conducted among 147 physical therapists using a structured questionnaire to collect demographic data and musculoskeletal pain characteristics. Prevalence rates for lifetime, one-year, and one-week periods were calculated along with associated factors such as job changes, activity limitation, and healthcare-seeking behavior. Results: The lifetime prevalence of low back pain was 81%, with 36.1% reporting pain in the last year and 66% in the past week. Neck pain lifetime prevalence was 59.2%, with 33.3% and 30.6% for one-year and one-week periods, respectively. Shoulder pain was reported by 29.9% of participants, with 12.9% experiencing right shoulder pain in the last year and 11.6% in the past week. Substantial proportions reported reduced work and leisure activities due to pain, with a notable number seeking medical care. Longer working hours and professional experience correlated with increased pain prevalence. Conclusion: Musculoskeletal pain, particularly low back pain, is highly prevalent among physical therapists, impacting their work and daily activities. Implementation of ergonomic strategies and preventive programs is critical to reduce MSD burden and promote occupational health in this professional group.